Fuzzy Genetic Grey Wolf based Deep Learning Model For Classification on Breast Cancer Dataset - et. al., A. Gopi Kannan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Neural Network is based on biological evolution of human brain. It is an emerging approach used to develop new and robust competing techniques. For solving learning and data analysis problems neural network techniques are used for better performance. In Medical data analysis, neural network, genetic and fuzzy techniques are widely used. In this paper, we proposed a new fuzzy genetic grey wolf based deep learning model on breast cancer dataset. Deep Convolution Neural Network (CNN) is an evolutionary algorithm, which mimics the process of human brain.CNN algorithm frequently used to solve classification problems. In medical domain, we need more accuracy when compared to other domains, because it closely related with the human life. Breast Cancer is one of the dangerous diseases among women in India as well as in the whole world.Deep learning based techniques has developed rapidly in recent years, mostly in classification. The proposed fuzzy genetic grey wolf based deep learning model produces better accuracy for classification on breast cancer dataset.